2016
DOI: 10.2807/1560-7917.es.2016.21.35.30333
|View full text |Cite
|
Sign up to set email alerts
|

Culex mosquitoes are experimentally unable to transmit Zika virus

Abstract: We report that two laboratory colonies of Culex quinquefasciatus and Culex pipiens mosquitoes were experimentally unable to transmit ZIKV either up to 21 days post an infectious blood meal or up to 14 days post intrathoracic inoculation. Infectious viral particles were detected in bodies, heads or saliva by a plaque forming unit assay on Vero cells. We therefore consider it unlikely that Culex mosquitoes are involved in the rapid spread of ZIKV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 25 publications
11
59
4
Order By: Relevance
“…The conclusions reported here regarding the inability of Culex mosquitoes to vector ZIKV correspond with a majority of recent studies addressing ZIKV transmission in Culex mosquitoes 2832. In contrast, two accounts report differing ZIKV transmission potential of Culex mosquitoes.…”
Section: Discussionsupporting
confidence: 86%
“…The conclusions reported here regarding the inability of Culex mosquitoes to vector ZIKV correspond with a majority of recent studies addressing ZIKV transmission in Culex mosquitoes 2832. In contrast, two accounts report differing ZIKV transmission potential of Culex mosquitoes.…”
Section: Discussionsupporting
confidence: 86%
“…Several reports have now shown Culex spp. to be refractory to infection [4145], including one field report [46]. Only one report has shown Culex to be susceptible to ZIKV infection [47].…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus mosquitoes may be competent vectors of ZIKV, several peer-reviewed studies utilizing mosquito populations from Brazil [41], Italy [42], Tunisia [43], the U.S. [36,43,44] demonstrated that these mosquitoes as well as Cx. pipiens are refractory to ZIKV infection and incapable of transmission.…”
Section: Transmission Cyclesmentioning
confidence: 99%